PROJECTION OF ECONOMIC GROWTH IN LEADING SECTORS IN THE REGION OF LOMBOK EAST REGENCY - Nia Kurniati; Syaumudinsyah Syaumudinsyah; Mey Susanti AS; Lubna Lubna (Jurnal Ekonomi, 2023)
This study aims to analyze the structure of the economy, leading sectors and projected economic growth in the leading sectors in 2024 in East Lombok Regency. The research method used is descriptive qualitative method. The data used is secondary data in the form of GRDP data by field of business at current prices and at constant prices, both for the area being analyzed, namely East Lombok Regency and for the reference area, namely West Nusa Tenggara Province. The data analysis technique used to determine the structure of the economy is using the Klassen Typology analysis. To analyze leading sectors using Location Quotient (LQ) analysis. Meanwhile, to analyze economic growth projections using Shift-Share analysis. The results of the study found that, based on the Klassen Typology analysis, there are 5 business sectors in quadrant I with the category of advanced and fast-growing sectors, quadrant II, there are 4 business sectors with the advanced sector category but depressed, quadrant III, there are 7 business sectors with the potential sector category or can still grow rapidly, and quadrant IV there is 1 business sector with relatively lagging sector categories. Analysis of Location Quotient (LQ) which has LQ> 1 means that it is a leading sector, there are 9 leading sectors in the East Lombok Regency area. Analysis of the economic growth projections for the leading sectors in 2014 for the East Lombok Regency as a whole is around 7.6%.